Methods of Solving Stereometry Problems Using Geogebra Software - S.Tanirbergenov; A.Kaldibaeva (International Journal of Medical Toxicology and Legal Medicine, 2024)
Among modern accessible digital tools that allow constructing and transforming geometric objects interactively, the GeoGebra environment is in increasing demand among teachers and researchers. However, analyzing printed and electronic sources, we can conclude that the issue of using GeoGebra in solving positional stereometric problems is not fully addressed. The features of solving positional stereometric problems using the GeoGebra 5.0 environment in geometry lessons in high school and when teaching image methods to future mathematics teachers at a pedagogical university are revealed. Emphasis is placed on the advantages of using GeoGebra in teaching the construction of spatial figures and their sections compared to traditional teaching.